Investigating the epistemic nature of STEM: analysis of science curriculum documents from the USA using the family resemblance approach - Park, W; Wu, J-Y; Erduran, S (Springer, 2020)
Although STEM education has been prevalent in curriculum policy and research literature, the precise epistemic nature of STEM and how it applies in education are relatively understudied. In this chapter, we use the framework of the Family Resemblance Approach (FRA) as a basis for highlighting the epistemic similarities and differences between the constituent STEM disciplines as represented in two US science curriculum documents. FRA allows for understanding constituent disciplines of STEM as members of a “family” that share particular features but also highlights domain specificity where particular knowledge and practices are specific to the respective disciplines. Our aim is to explore the affordances of FRA in clarifying the epistemic nature of STEM and in contributing to curriculum analysis. To do this, we present an analysis of the US Science for All Americans and the Next Generation Science Standards to examine their coverage of epistemic underpinnings of STEM disciplines and discuss implications for curriculum policy.